Bimbingan Spiritual dalam Membentuk Resiliensi Korban Penyalahgunaan Narkotika di Yayasan Sakinah Harakah Bhakti (Sahabat Foundation) Tangerang Selatan, Banten - Andika Nugraha; Moh. Amin Tohari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Drugs are an abbreviation of narcotics, psychotropics, and hazardous materials. Narcotics are addictive substances or materials that work on the nervous system, can cause loss of consciousness and pain, and can cause dependence. Psychotropics are substances or active materials that work on the central nervous system, can cause changes in mental activity and behavior, and can cause dependence. To deal with this problem, one of them is through the Sakinah Harakah Bhakti Center Foundation (Sahabat Foundation) South Tangerang, Banten which provides treatment to develop psychological strength called resilience through spiritual guidance. Through spiritual guidance, it is hoped that it will be able to form the resilience of drug abuse students so that they are able to bounce back from various pressures and face the next life with a better perspective. The purpose of this study was to determine how spiritual guidance activities in forming the resilience of drug abuse students at the Sakinah Harakah Bhakti Foundation (Sahabat Foundation). The research method used is qualitative with a descriptive type. The subjects in this study consisted of 1 Foundation administrator, 1 spiritual guide, and 3 beneficiaries (PM) of drug abuse. Through interviews and observations, it is known that spiritual guidance activities at the Sakinah Harakah Bhakti Foundation (Sahabat Foundation) are muhasabah, sirah nabawiyah, theory and practice of worship, and thematic interpretation.